The Effects of a Problem-Based Learning Model Aided by Mind Mapping on Self-directed Learning in Elementary School Students (Universitas Negeri Semarang, 2022)
Self-directed learning in schools has not shown positive results, especially in fifth grade students. Several surveys show that they still do not have an attitude toward self-directed learning. The problem-based learning model and mind mapping respectively has characteristics that can train this attitude. So, this study aims to analyze the effectiveness of the problem-based learning model with the aid of mind mapping in increasing self-directed learning in fifth-grade elementary school students. This research design used an experimental method with a pretest-posttest control group design by analyzing quantitative data on the effectiveness of the Problem-based learning model with the aid of mind mapping on the self-directed learning of elementary school students. The research sample was the fifth-grade students of Randegan Kulon I Primary Schools in Majalengka Regency as the experimental class and class V of Randegan Kulon II Primary School in Majalengka Regency as the control class. Data collection was obtained through a self-directed learning questionnaire sheet. The data obtained were analyzed using the classical completeness test, independent T-test, and N-gain test. The results showed that the Problem-based learning model assisted by mind mapping was effective in increasing the self-directed learning of students by showing: (a) the classical mastery score reached 93.75%, (b) the average score reached 81, (c) and the N-gain value reached 0 .50 in the medium category. Based on the analysis results, it was concluded that the problem-based learning model assisted by mind mapping was effective in increasing the self-directed learning of students.